Analisis Usahatani Sayuran di Kecamatan Telaga Langsat Kabupaten Hutu Sungai Selatan - Mawaddatina Mawaddatina; Artahnan Aid; Djoko Santoso (Universitas Lambung Mangkurat, 2013)
From economic point of view, vegetable is a significant source of income for community since it is high value product. Moreover, vegetables cen generate addition income for the country through international trade. The purposes of the study are to explore: (1) cost, revenue, and profit of vegetables cultivation; (2) the break-even point of multi-product; and (3) the farmer decision to diversify the vegetables at the study site. The implicit cost of the cultivation is IDR 57. 94 million per hectare, while the explicit cost is !DR 36. 98 million per hectare. The revenue and profit generated are as much as IDR 711.07 million and IDR 43.27 million per hectare, separately. The break-even point is reached at the production level of 1.759.73 kg. The motives to diversify are because of vegetables price, cut pest and disease cycle cut, the ease of cultivation, the use of fallowed land, and small capital required.